Vancomycin in anterior cruciate ligament graft preparation; does it really reduce infection rate? - Osman, Sari M.; Lawati, Ali Abdullah Mohammed Al (International Journal of Research in Orthopaedics, 2025)
Background: The aim of our study is to evaluate how the incidence of septic arthritis or postoperative infection is affected by the use of vancomycin in preparation of grafts during anterior cruciate ligament (ACL) reconstruction. Methods: This is a retrospective comparative study conducted between two groups, first group operated in the period from August 2017 to August 2018, second group operated in the period from December 2022 to December 2023. It focuses on the incidence of post-operative infection rate in ACL reconstruction surgeries. All patients who had ACL reconstruction were included, all surgeries were performed by a single surgeon at the same hospital with the same set up and consumables. Infection was defined as a return to the operating room for irrigation and debridement within 90 days after surgery. Results: Total of 130 patients were included in the study, first group (vancomycin group) or second group (non-vancomycin group) no patients suffered from postoperative deep infection, neither on the immediate post operative follow up, nor at the end of their final follow up. Comparing the two groups, more revision anterior cruciate reconstructions included in the second group, yet no single case of infection took place in any of the two groups. Conclusions: In conclusion we found no difference between adding vancomycin to the graft or not adding it, as both groups showed no infection.